Implementation and quality assessment of a pharmacy services call center for outpatient pharmacies and specialty pharmacy services in an academic health system. (15th May 2018) - Rim, Matthew H.; Thomas, Karen C.; Chandramouli, Jane; Barrus, Stephanie A.; Nickman, Nancy A.
Abstract : Purpose: The implementation and quality assessment of a pharmacy services call center (PSCC) for outpatient pharmacies and specialty pharmacy services within an academic health system are described. Summary: Prolonged wait times in outpatient pharmacies or hold times on the phone affect the ability of pharmacies to capture and retain prescriptions. To support outpatient pharmacy operations and improve quality, a PSCC was developed to centralize handling of all outpatient and specialty pharmacy calls. The purpose of the PSCC was to improve the quality of pharmacy telephone services by (1) decreasing the call abandonment rate, (2) improving the speed of answer, (3) increasing first-call resolution, (4) centralizing all specialty pharmacy and prior authorization calls, (5) increasing labor efficiency and pharmacy capacities, (6) implementing a quality evaluation program, and (7) improving workplace satisfaction and retention of outpatient pharmacy staff. The PSCC centralized pharmacy calls from 9 pharmacy locations, 2 outpatient clinics, and a specialty pharmacy. Since implementation, the PSCC has achieved and maintained program goals, including improved abandonment rate, speed of answer, and first-call resolution. A centralized 24-7 support line for specialty pharmacy patients was also successfully established. A quality calibration program was implemented to ensure service quality and excellent patient experience. Additional ongoing evaluations measure the impact of the PSCC on improving workplace satisfaction and retention of outpatient pharmacy staff. Conclusion: The design and implementation of the PSCC have significantly improved the health system's patient experiences, efficiency, and quality.